Mutual interaction between literature and architectural space - Ainash, Nauryzbayeva; Yussupova, Ardak; Nurpeiis, Moldir; Sadvokasova, Gaukhar; Trofimov, Victor; Myrzakhmetova, Saltanat (Linguistics and Culture Review, 2021)
Examples of the interaction of literature and architectural space are considered in this article. The considered examples demonstrate the role of literature in solving various architectural problems. For example, social tasks related to the safety of the urban environment, in the creation of a unique image of the city, the development of stylistic trends, environmental problems. Human perception of architectural space, described in the literature, can make an invaluable contribution to scientific research in the social and humanitarian direction. The description of architectural spaces allows us to identify the level of comfort, the influence of architectural objects and landscape on people, the correspondence of the urban environment to the worldview of the townspeople. Both directions have huge scientific potential in research activities. The result of this research is the interpretation of the literary description of the subject environment of applied folk art in a modern interior. The architectural space has a scenic character reflecting the literary descriptions of the yurt's interior. This approach can be used as the main direction in the development of the concept of architectural spaces for different functional purposes. This article examines an example of a kindergarten organized according to the principle of "the walls teach".